2011
DOI: 10.1007/s10592-011-0194-0
|View full text |Cite
|
Sign up to set email alerts
|

Effective population size is strongly correlated with breeding pond size in the endangered California tiger salamander, Ambystoma californiense

Abstract: Maintaining genetic diversity and population viability in endangered and threatened species is a primary concern of conservation biology. Genetic diversity depends on population connectivity and effective population size (N e ), both of which are often compromised in endangered taxa. While the importance of population connectivity and gene flow has been well studied, investigating effective population sizes in natural systems has received far less attention. However, N e plays a prominent role in the maintenan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
57
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(66 citation statements)
references
References 71 publications
(98 reference statements)
9
57
0
Order By: Relevance
“…Genetic N e estimates were on the same order as other salamanders (Funk et al 1999;Wang et al 2011) and amphibians (Rowe and BeeBee 2004). Reviews across wild populations of various taxa have found N e estimates to be considerably lower than census size (Frankham 1995).…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Genetic N e estimates were on the same order as other salamanders (Funk et al 1999;Wang et al 2011) and amphibians (Rowe and BeeBee 2004). Reviews across wild populations of various taxa have found N e estimates to be considerably lower than census size (Frankham 1995).…”
Section: Discussionmentioning
confidence: 81%
“…Many amphibian populations are characterized as metapopulations, with individual breeding ponds acting as local subpopulations subject to stochastic extinctions and recolonizations over time (Marsh and Trenham 2001). Breeding ponds have been identified as separate genetic units in multiple studies, with both the quality of habitat and population abundance at the pond having been found to correlate with pond level N e or N b (Gamble et al 2007;Greenwald et al 2009;Wang et al 2011;Whiteley et al 2014). These results suggest that genetic diversity at the pond level is distinct from the overall metapopulation and understanding N b within ponds is important and informative.…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al. ). This suggests that effective population sizes of the studied populations are not above a threshold that prevents the loss of genetic diversity and/or that the high potential for gene flow suggested by the subtle patterns of genetic structure observed in this species is not sufficient to counterbalance the effects of genetic drift (Lange et al.…”
Section: Discussionmentioning
confidence: 99%
“…It is, however, extremely difficult to characterize the extent to which the species has declined through direct observation given their cryptic nature and the difficulties in finding and accessing many of their breeding sites. To better understand the demography of CTS populations, Wang et al (2011) used microsatellites to explore several aspects of within-population processes in 10 ponds in Merced County, California. They found that ponds generally had small effective population sizes (an average of 30) and that effective population sizes were highly correlated with the size of the breeding ponds where animals were sampled (particularly true for natural breeding pools, less so for human-constructed ones).…”
Section: Methods and Their Applications To Amphibiansmentioning
confidence: 99%
“…A key finding of several of the studies in Table 2 is the different patterns seen over diverse scales and sampling regimes. For instance, researchers have found differing effects of landscapes on amphibians by looking at different regions inhabited by a single species (Johansson et al 2005;Wang et al 2009aWang et al , 2011Moore et al 2011;Trumbo et al 2013), different species within the same region (Goldberg & Waits 2010;Richardson 2012), different time periods for the same metapopulation (Savage et al 2010) and different spatial scales for the same analysis (Angelone et al 2011). These results collectively challenge the generality of results that stem from landscape genetic studies, and suggest that results from molecular studies of amphibian-landscape interactions should generally be interpreted within the scope of a specific study or region, but not beyond.…”
Section: Amphibian Conservationmentioning
confidence: 99%